Molecular characterization of Echinococcus granulosus cysts in north Indian patients: identification of G1, G3, G5 and G6 genotypes. - Monika Sharma; Rakesh Sehgal; Bashir Ahmad Fomda; Anil Malhotra; Nancy Malla (Public Library of Science (PLoS), 2013)
BACKGROUND: Cystic echinococcosis (CE) caused by the Echinococcus granulosus, is a major public health problem worldwide, including India. The different genotypes of E. granulosus responsible for human hydatidosis have been reported from endemic areas throughout the world. However, the genetic characterization of E. granulosus infecting the human population in India is lacking. The aim of study was to ascertain the genotype(s) of the parasite responsible for human hydatidosis in North India. METHODOLOGY/PRINCIPAL FINDINGS: To study the transmission patterns of E. granulosus, genotypic analysis was performed on hydatid cysts obtained from 32 cystic echinococcosis (CE) patients residing in 7 different states of North India. Mitochondrial cytochrome c oxidase subunit1 (cox1) sequencing was done for molecular identification of the isolates. Most of the CE patients (30/32) were found to be infected with hydatid cyst of either G3 (53.1%) or G1 (40.62%) genotype and one each of G5 (cattle strain) and G6 (camel strain) genotype. CONCLUSIONS/SIGNIFICANCE: These findings demonstrate the zoonotic potential of G1 (sheep strain) and G3 (buffalo strain) genotypes of E. granulosus as these emerged as predominant genotypes infecting the humans in India. In addition to this, the present study reports the first human CE case infected with G5 genotype (cattle strain) in an Asian country and presence of G6 genotype (camel strain) in India. The results may have important implications in the planning of control strategies for human hydatidosis.